2018
DOI: 10.1002/cem.3088
|View full text |Cite
|
Sign up to set email alerts
|

Localized and adaptive soft sensor based on an extreme learning machine with automated self‐correction strategies

Abstract: A novel, nonlinear soft sensor based on a localized, adaptive single-layer feedforward neural network with random hidden layer weights, also called an extreme learning machine, combined with the recursive partial least squares algorithm to update the linear output layer weights, is explored. The soft sensor is highly adaptive with minimal operator input, and automated mechanisms are included to self-correct numerous aspects of the underlying model.For instance, mechanisms are put in place to automatically sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…The most common types of ANN are multi-layer perceptron (MLP) and radial basis function networks (RBFN). The literature has shown that ANN is especially suitable for implementation of soft sensors, and these have indeed been used [38,39,40,41,42,43,44,45,46,47]. More recently, deep learning has been used to create soft sensors also successfully [48,49,50,51].…”
Section: Introductionmentioning
confidence: 99%
“…The most common types of ANN are multi-layer perceptron (MLP) and radial basis function networks (RBFN). The literature has shown that ANN is especially suitable for implementation of soft sensors, and these have indeed been used [38,39,40,41,42,43,44,45,46,47]. More recently, deep learning has been used to create soft sensors also successfully [48,49,50,51].…”
Section: Introductionmentioning
confidence: 99%